The Effect of Moringa Leaf Capsule on the Hemoglobin Levels in Young Women at Smp Sabbihisma Padang - Sartika, Wiwi; ., Herwati; Suryarinilsih, Yossi (KnE Life Sciences, 2019)
In adolescents, the iron not only functions as energy metabolism in the body but also helps to improve learning achievement. Iron deficiency can lead to fatigue, and the concentration, memory and learning abilities can be disrupted. It can also lead to anemia, especially in young women. The purpose of this study was to determine the effect of leaf moringa capsules on the hemoglobin levels in adolescent girls in Sabbihisma Junior High School. This research used a quasi method of pretest and posttest experiment with control group design. The sample of the study were 32 people, 16 cases (moringa leaf capsule) and 16 control groups. Data collection was done through observation and laboratory examination of hemoglobin levels before and after treatment. The data were tested with paired sample t-test. The results showed that there was a significant difference in female hemoglobin levels in the case group with p = 0,000, while the control group was not significant with p = 0,091.